(untitled) (Jurnal Simki Economic, 2024)
This research analyzes the determination of selling prices in the thrifting business at @MOZZA.THRIIFT. The purpose of this study is to identify factors that influence the determination of selling prices and provide recommendations for effective pricing strategies. The research method used is a qualitative approach with interviews with the owner and manager of @MOZZA.THRIIFT and secondary data analysis. The analysis was used to identify factors that influence pricing, and analysis was used to formulate pricing strategies. The research findings show that product quality, brand, market demand, and economic conditions affect pricing in thrifting businesses. Pricing strategy recommendations include price differentiation based on product quality and condition, dynamic pricing, and appropriate sales promotion. The implication of this research is the importance of paying attention to these factors in determining the optimal selling so that thrifting businesses can increase their profits and competitiveness. The results of this study can be a guide for thrift business owners and managers in optimizing pricing strategies to achieve success in the thrifting industry.